(untitled) (Journal of Applied Learning and Teaching, 2024)
This opinion piece offers an overview of why innovative practices in strategic management and leadership have an essential role in the long-term success of higher educational institutions. Additionally, it examines the strategies that can help universities maintain a competitive advantage in a complex global environment, opening business opportunities and providing better prospects for students, academics and society. I present the case of Greek Universities, with evidence from interviews with academics and my experience as an academic in several academic institutions for 17 years. For the purposes of this article, innovative practices in universities also engage creativity processes and design how students and academics can and need to share opportunities, co-create and initiate innovative behaviours.